### Ex: Write an expression to describe a rule for the sequence: -1, 4, 9, 14, 19,... Then find the 90th term.
Answer: Rule: 5n - 6 (Since the difference from -1 to 4, and from 4 to 9, and from 9 to 14 etc. is 5, I start by writing 5n. Then, I plug in n = 1 to see if my first value is off or not. For n = 1, 5n becomes 5*1 = 5. Since the first term of the sequence is - 1 not 5, we need to subtract 6. Our formula is now 5n - 6. Check to make sure the formula works for n =2, n = 3, etc.
To find the 90th terms, plug in n = 90 in the expression.
We now have: 5 * (90) - 6 = 450 - 6 = 444.
The 90th terms is equal to 444.